Experience with botulinum toxin type A in the treatment of neurogenic detrusor overactivity in clinical practice - Stephanie Knuepfer; Klaus-Peter Juenemann (Therapeutic Advances in Urology, 2014)
Control of the lower urinary tract is a complex, multilevel process that involves both the peripheral and central nervous system. Neurogenic lower urinary tract dysfunction (LUTD) is a widespread chronic illness that impairs millions of people worldwide. Neurogenic LUTD has a major impact on quality of life, affecting emotional, social, sexual, occupational and physical aspects of daily life, and in addition to the debilitating manifestations for patients, it also imposes a substantial economic burden on every healthcare system. First-line treatment for neurogenic LUTD includes antimuscarinics and some form of catheterization, preferably intermittent self-catheterization. However, the treatment effect is often unsatisfactory, so that other options have to be considered. Moreover, neurogenic LUTD is a challenge because all available treatment modalities (i.e. conservative, minimally invasive and invasive therapies) may fail. In recent years, botulinum neurotoxin type A (BoNT/A) treatment has been shown to be an effective pharmacological therapy option in patients refractory to antimuscarinic and neurogenic detrusor overactivity (NDO). Several studies have shown that BoNT/A injection significantly reduces detrusor muscle overactivity. Also BoNT/A treatment of NDO has revealed a significant improvement of lower urinary tract function with regard to reduced urinary incontinence, reduced detrusor pressure, increased bladder capacity and improved quality of life in NDO.